An intelligent approach to security. Issue 2 (February 2015) - Beckett, Phil
Abstract : Research by PwC earlier on this year suggested that the cost of cyber-security to businesses has doubled in the past four years as cyber threats increase and firms battle to protect themselves. 1 As hackers develop sophisticated methods to penetrate security efforts, the threats of cyber-security breaches continue to have a large prominence in the mind of management teams across all types of businesses.